The Influence of Teacher Expectations about Twice-Exceptional Students on the Use of High Quality Gifted Curriculum: A Case Study Approach. Issue 1 (2nd January 2016) - Missett, Tracy C.; Azano, Amy Price; Callahan, Carolyn M.; Landrum, Kimberly
ABSTRACT: Twice-exceptional students show evidence of high academic performance or potential and also have a disability that impedes their ability to learn. Twice-exceptional students remain under-represented in gifted programs, and some researchers attribute such under-representation to the negative beliefs and low expectations about twice-exceptional students held by teachers. While researchers have begun to investigate the curricular models and instructional strategies that are effective for twice-exceptional students, little research addresses how teacher beliefs and expectations about student ability are reflected in the ways teachers implement such models and strategies for twice-exceptional students in gifted classrooms. Even less research addresses gifted students with emotional and behavioral disabilities. We used a case study of a third-grade teacher using a structured, model-based language arts curriculum to better understand how her expectations about a gifted student with an emotional disability influenced her instructional choices. Using observational and interview data, the case study approach allowed the researchers to personalize the experiences of this teacher and provided a context in which to examine the subtleties of teacher expectations when teaching a gifted student with an emotional disability. Implications for educational practice, particularly the need for comprehensive school-based support systems for students with emotional disabilities, are discussed.